A STUDY OF RELATIONSHIP BETWEEN STRATEGIC ENTREPRENEURSHIP AND COMPETITIVE ADVANTAGE - Bashir, Shahzada Irfan; Vij, Sandeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Purpose- This firm-level study is based on a primary survey of 235 key informants from the manufacturing and service organizations of small and medium enterprises (SMEs) in the State of Punjab, India. It empirically tests the relationship between strategic entrepreneurship and competitive advantage. Design/methodology/approach- The study adopted a cross-sectional research design, using a purposive sampling technique to gather data from firms. We utilized a self-designed, undisguised questionnaire for data collection. Findings- The study reveals a strong relationship between strategic entrepreneurship and competitive advantage. It suggests that practicing managers should simultaneously adopt opportunity-seeking and advantage-seeking behaviors for gaining a competitive advantage. Originality- The study contributes to strategic management literature by developing and validating a scale for strategic entrepreneurship and establishing its positive relationship with competitive advantage. Research limitations/implications- The findings of the study can guide researchers and practitioners in strategic entrepreneurship to understand its role in gaining sustainable competitive advantage. Future researchers can build on the findings of this study for a richer understanding of strategic entrepreneurship and its role in competitive advantage.